Modelling and shadowgraph imaging of cocrystal dissolution and assessment of in vitro antimicrobial activity for sulfadimidine/4-aminosalicylic acid cocrystals - HEALY, ANNE; D'ARCY, DEIRDRE; PERSOONS, TIM (My University, 2016)
Purpose: The aim of this work was to evaluate the influence of crystal habit on the dissolution and in vitro antibacterial and anitiprotozoal activity of sulfadimidine:4-aminosalicylic acid cocrystals. Methods: Cocrystals were produced via milling or solvent mediated processes. In vitro dissolution was carried out in the flow-through apparatus, with shadowgraph imaging and mechanistic mathematical models used to observe and simulate particle dissolution. In vitro activity was tested using agar diffusion assays. Results: Cocrystallisation via milling produced small polyhedral crystals with antimicrobial activity significantly higher than sulfadimidine alone, consistent with a fast dissolution rate which was matched only by cocrystals which were milled following solvent evaporation. Cocrystallisation by solvent evaporation (ethanol, acetone) or spray drying produced flattened, plate-like or quasi-spherical cocrystals, respectively, with more hydrophobic surfaces and greater tendency to form aggregates in aqueous media, limiting both the dissolution rate and in vitro activity. Deviation from predicted dissolution profiles was attributable to aggregation behaviour, supported by observations from shadowgraph imaging. Conclusions: Aggregation behaviour during dissolution of cocrystals with different habits affected the dissolution rate, consistent with in vitro activity. Combining mechanistic models with shadowgraph imaging is a valuable approach for dissolution process analysis.
PUBLISHED
Keywords: Cocrystal, crystal habit, shadowgraph imaging, particle tracking velocimetry, dissolution simulation, flow-through cell, aggregation; Cocrystal, crystal habit, shadowgraph imaging, particle tracking velocimetry, dissolution simulation, flow-through cell, aggregation; Nanoscience & Materials; DISSOLUTION RATES